Development of The Means of Engagement Concept on Enterprise Resource Planning User Satisfaction - Rafsanjani, Rayhan Rafael; Lubis, Muharman; Abdulmana, Sahidan (Electronic Integrated Computer Algorithm Journal, 2023)
None of the several theories that underpin the assessment of IT adoption characterizes the process as dynamically as the Means of Engagement theory does. User satisfaction is a key factor in influencing the success of ERP implementation as well as the adoption of the ERP system by the user. Therefore, it is necessary to identify the factors affecting user satisfaction of the ERP system as well as the relationship between customer satisfaction and user involvement. This research aims to develop a concept or model of Means of Engagement (MOE) on relationship domain in particular for satisfaction factor with the research object of PT Glico Indonesia. The research uses SEM-PLS analysis method using the SmartPLS 4 application to construct and test a structural equation model that reflects the relationship between the variables investigated in the research. The evaluation results showed that the five SERVQUAL dimensions studied did not have a significant impact on user satisfaction while customer satisfaction had a significant positive impact on engagement. The results of this research, namely the development of the Means of Engagement model, are expected to be the basis for PT Glico Indonesia to design strategies that can improve and maintain the adoption of ERP system users based on the level of the means of engagement model.